Adolescent Menstrual Hygiene Education and Screening: "Haid Bersih" Guidelines for Wetland Areas - Tampubolon, Masrina Munawarah; Misrawati, Misrawati; Dewi, Yulia Irvani; Utami, Sri; Erika, Erika; Suci, Wice Purwani; Aulia, Nur; Lestari, Widia (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT Adolescents in Pekanbaru face significant reproductive health challenges, including anemia, vaginal discharge, and menstrual pain. Many students are hesitant to take the blood supplement tablets provided by the UKS and lack education on menstrual hygiene management. To address these issues, the team developed the "Haid Bersih" module. The initiative aims to deliver promotional and preventive services, as well as education on menstrual hygiene management, aligning with University IKU 3 and 5. The methods employed include reproductive health screening and menstrual hygiene education. Screening is conducted for both female and male students using a questionnaire that covers access to counselling, menstrual experiences, reproductive health problems, and incidents of sexual violence. The "Haid Bersih" module specifically provides guidelines for menstrual hygiene in wetland areas. The results indicated enthusiastic reception of the educational activities by UKS students, teachers, and nurses. Students received booklets and accessed information through posters and QR codes for screening. The screening revealed that while the majority of adolescent girls had received counselling on puberty and sexually transmitted disease prevention, sexual health education remained minimal. Many girls reported discomfort during menstruation and other reproductive health issues. Generally, male students exhibited signs of puberty. There is a clear need for further education and enhanced digital literacy among adolescents to access reproductive and sexual health information. These findings highlight the necessity of a comprehensive approach to addressing adolescent reproductive health in Pekanbaru Keywords: Adolescent Reproductive Health, Menstrual Hygiene Management, Adolescent Screening